+0  
 
0
143
1
avatar+1015 

 

What is the inverse of the function?

AngelRay  Mar 3, 2018
 #1
avatar+13638 
+1

y = x^(x-1)     solve for 'x

log (y) = (x-1) log 3

 

log(y) /log 3 = (x-1)              Remember:   Switching log bases:   Logb(a) =  log(a) / log(b)

log3 (y) = x-1

log3(y) + 1 = x                    Now switch the y's and x's

y = log3(x) + 1

f'(x) = log3(x) + 1

ElectricPavlov  Mar 4, 2018

14 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.